DEKONSTRUKSI PERBUATAN AKHLAKI AKUNTAN PROFESIONAL BERBASIS TRANSFORMASI DIRI “NAFS” - Ida Ayu Nursanty (Valid: Jurnal Ilmiah, 2016)
Ethical dilemmas arise as a consequence of conflicts audit because the auditor is in a situation of decision-making between ethical and unethical. The situation in the conflict are formed because there are parties interested in the auditor's decision, which auditors faced with a decision between ethical and unethical. Thus the focus of this study is how an accountant take the right decision. With the concept of self-transformation "nafs" of the tyrannical nafs to the level of the highest known “pure nafs” so accountant obtain glory itself is akhlaki Islamic accountant